Improving students’ environmental awareness through Project-Based Learning (PBL): A case at a secondary high school in Karawang - Sidik Indra Nugraha; Iwan Ridwan (ELT in Focus, 2019)
The environment in which we are living is an important and inseparable part of human life. Any environmental degradation therefore will have both direct and indirect impact on human and other living creatures. This research is aimed at exploring the implementation of PBL and the students’ responses towards the implementation of PBL especially in relation to the ways the students learn English as well as raising students’ environmental awareness. Employing qualitative case study, this research was conducted at a secondary high school in Karawang. Twenty students of grade eleven participated in this research. The data were collected through classroom observation and interview. The result indicated that the PBL was implemented through several stages, i.e. preparation, designing the project, executing the project, project presentation, and evaluation. The analysis also revealed the students’ responses towards the implementation of PBL. It can be concluded that the students responded quite positively towards the implementation of PBL as an effort to improve the students’ writing ability as well as their awareness towards environmental issues. Besides its benefits, there are several concerns found related to implementing PBL including learning management, group work distribution, and facilities.